O processo de tomada de consciência em idosos agricultores egressos da EJAI quanto à mobilização dos saberes escolares nas lidas cotidianas - Peruzzo, Flávia (2021)
The scope of research on population aging has assumed significant complexity and breadth over the last two decades. This is due, above all, to the increase in the elderly population, and to public policies aimed at this expressive portion of society. The present study originates fundamentally from the understanding that education can and should contribute to the resignification processes of this new old age. The history of denial or exclusion of today's elderly cannot justify the denial of their right to access other knowledge and establish new connections. The general theme of this research is about the process of awareness regarding the mobilization of school knowledge in elderly farmers coming from the Education of Youth, Adults and Elderly (EJAI), in the modality of high school, in a rural community in Concordia, SC, from the problematization of daily tasks on rural properties. The main objective is to study the process of Awareness Raising regarding the mobilization of school knowledge in elderly farmers who graduated from EJAI. The specific objectives are: to seek, in the context of academic research, the production of knowledge about old age and lifelong learning processes; panoramicly systematize the Psychology of Aging from the perspective of learning and cognition of the elderly; address the context of human aging in terms of nomenclature, legislation, national and local circumstances. The central question of the thesis to be answered is: At what levels are the manifestations of Awareness of the elderly farmers who graduated from the process of secondary school education, regarding the mobilization of school knowledge in the operationalization of daily tasks? The study is also guided by two adjacent questions: To what extent has the context of schooling in the so-called 'regular age' influenced conceptual levels in elderly life? What is the importance of the school institution in the lives of these elderly subjects? The theoretical option that supports the research is anchored in three aspects: a) in Jean Piaget's theory of human development (1977; 1978), especially with regard to the process of awareness; b) in the psychology of aging by Paul Baltes (1980; 1987), which supports the paradigm of human development throughout life, assuming it as a multidirectional and multifunctional process, influenced by historical, psychological, biological, social and cultural factors; c) in the social context of old age based on the approach of Anita Liberalesso Neri. The investigative processes are anchored in the Piagetian clinical method, guided by problem-situations of daily life. The basic strategies used in the context of this investigation were clinical intervention with crosswords - involving school and everyday knowledge - and field observation in the cultivation of the home garden. Peripheral instruments were also used, such as semi-structured interviews and databases produced in the research of the Master's Degree by the author of this thesis. The subjects of this research are five elderly farmers living in the rural area of the municipality of Concordia/SC, aged between 60 and 70 years, three women and two men, graduates of a Schooling Program for EJAI that began in 2010, with literacy courses initial, and ended with high school in 2017. It was concluded that each researched subject manifests their Consciousness in different proportions and situations based on the experiences they have experienced over their years. This result is consistent with Piaget's (1983) position, according to which there is no hermetic chronology for the appropriation of knowledge, but a successive order that is variable and subordinated to the subjects' previous experiences, to social transmissions. , its maturation and, essentially, the social environment that can accelerate or delay the advent of a stage, or even inhibit its manifestation. Thus, it appears that one does not become old or old at an agreed age and, in this perspective, aging is a matter of the experience of one's own existence.